2020
DOI: 10.3389/fphar.2020.00890
|View full text |Cite
|
Sign up to set email alerts
|

Initial Dosage Recommendation for Sirolimus in Children With Tuberous Sclerosis Complex

Abstract: Sirolimus is already used in the treatment of tuberous sclerosis complex (TSC), however, with narrow therapeutic range and considerable inter-and intra-individual pharmacokinetic variability, making it hard to develop an appropriate sirolimus initial dosage regimen, especially in children with TSC. The aim of this study was to recommend the optimal sirolimus initial dosing regimen in pediatric patients with TSC. Underlying physiological and genetic factors were collected to explore the effects on clinical siro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 27 publications
0
36
0
Order By: Relevance
“…Of course, to some extent, CYP3A4 and CYP3A5 may influence sirolimus metabolism in adults (Tamashiro et al, 2017;Zhang et al, 2017). However, it was interesting in our previous study that the initial dosage recommendation for sirolimus in children with TSC, CYP3A4, and CYP3A5 polymorphism did not significantly affect sirolimus clearance rates (Wang et al, 2020). The main reason was that included children had a wide age span (Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Of course, to some extent, CYP3A4 and CYP3A5 may influence sirolimus metabolism in adults (Tamashiro et al, 2017;Zhang et al, 2017). However, it was interesting in our previous study that the initial dosage recommendation for sirolimus in children with TSC, CYP3A4, and CYP3A5 polymorphism did not significantly affect sirolimus clearance rates (Wang et al, 2020). The main reason was that included children had a wide age span (Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 94%
“…However, it was interesting in our previous study that the initial dosage recommendation for sirolimus in children with TSC, CYP3A4, and CYP3A5 polymorphism did not significantly affect sirolimus clearance rates (Wang et al, 2020). The main reason was that included children had a wide age span (Wang et al, 2020). And it was reported that gene expression in different age development processes had development-dependent characteristics; meanwhile, CYP3A expression isoforms levels were highly variable after birth (Lacroix et al, 1997).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations